P362 Seasonal trend of fungal flora in water of tertiary care hospital in North India. (20th September 2022) - Mahajan, Monika; Kaur, Harsimran; Rudramurthy, Shivaprakash M; Biswal, Manisha; Ray, Pallab
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM: Objectives: The study was conducted to assess the seasonal variation of fungal flora in hospital water of a tertiary care hospital in North India. Methods: A total of 200 water samples from the main reservoir, overhead and underground tanks, and taps of critical care units of the hospital were collected. The water samples were filtered by membrane filtration technique (0.22 micron) and cultured on dichloran rose-Bengal chloramphenicol agar with and without benomyl. The plates were incubated for upto 15 days and fungal colonies recovered were sub-cultured on Sabouraud Dextrose Agar and identified by phenotypic methods. Yeasts were identified by Matrix Assisted Laser Desorption Ionization Time of Flight (MALDI-TOF-MS). Results: Mycelial fungi were isolated from 100% of the water samples which included Alternaria, Curvularia, Nigrospora, Penicillium, Aspergillus, Paecilomyces, Scytillidium, and Mycelia sterilia as depicted in Figure 1. Different fungi were prevailing in different water storage units like: Advance eye center— A. fumigatus, A. flavus, Fusarium solani, Alternaria spp . Rhizopus arrhizus, Ustilago spp., mycelia sterilia, Trichosporon spp.; Advance trauma Center— Cladophaialophora spp., Alternaria alternata, Penicillium, spp. A. flavus, A. nidulans, A. fumigatus, F. solani, Rhodotorula spp.: Bone marrow transplant unit— Alterneria alternata, A. niger, A. flavus, A. versicolor, Cladosporium spp., Fonsecaea pedrosoi, Fusarium spp., Nigrospora spherica, Penicillium spp., Rhodotorula spp., Trichosporon ashaii . The seasonal variation of fungal isolation is depicted in Figure 2. Isolation rate of Aspergillus species was 35% in winters, 31% in post-monsoon, 25% in summers. Isolation rate of Penicillium species was 19% in post-monsoon, 16% in winter and 15% in summers. Maximum number of dematiaceous fungi were isolated in summer season with isolation rate of 30% in summers as compared with 21.5% in post-monsoon and 19% in winters. Few yeasts isolated were Rhodotorula, Trichosporon, and Ustilago . Mucorales isolated rarely included Rhizopus, Absidia, Syncephalastrum, and Mucor species. Fungal colony forming units in the water samples ranged from 50 to 450 colony forming units/liter of water. Conclusion: The distribution of fungi in hospital water showed diversity and seasonal variability. Aspergillus species were isolated in maximum number in the winter season, Penicillium species in post-monsoon season and dematiaceous fungi in the winter season. Water as a source of fungal infection in critical care units, remains a relatively neglected area. Water supply could be a source of nosocomial fungal infections. Improving the quality of water by regular testing for fungal contamination and appropriate action to reduce its burden may reduce the hospital-acquired fungal infections.